Analytical solution for statif bending analyses of functionally grades plates with porosities - Slimane Merdaci; Adda Hadj Mostefa; Youcef Beldjelili; Mohamed Merazi; Sabrina Boutaleb; Hadjira Hellal (Fracture and Structural Integrity)
The paper examines a static bending of porous functional plates (FGP) and rectangular plate solutions, based on an underlying high-order shear deformation theory. The proposed high-order shear deformation theory, as opposed to other theories, includes four unknowns. For this reason, a new shear strain function is considered. The technique of Navier is used in closed-form FGP solutions. Results of deflections and stresses are presented for simply supported border conditions. Current figures are contrasted with the non-poreous plate deflecting solutions and the literature's stresses. Effects of different parameters, including thickness, gradient index and porosity of FGM plates, are discussed.